Targeting surface nucleolin with a multivalent pseudopeptide delays development of spontaneous melanoma in RET transgenic mice - El Khoury, Diala (BioMed Central, 2010)
BACKGROUND: The importance of cell-surface nucleolin in cancer biology was recently highlighted by studies showing that ligands of nucleolin play critical role in tumorigenesis and angiogenesis. By using a specific antagonist that binds the C-terminal tail of nucleolin, the HB-19 pseudopeptide, we recently reported that HB-19 treatment markedly suppressed the progression of established human breast tumor cell xenografts in the athymic nude mice without apparent toxicity. METHODS: The in vivo antitumoral action of HB-19 treatment was assessed on the spontaneous development of melanoma in the RET transgenic mouse model. Ten days old RET mice were treated with HB-19 in a prophylactic setting that extended 300 days. In parallel, the molecular basis for the action of HB-19 was investigated on a melanoma cell line (called TIII) derived from a cutaneous nodule of a RET mouse. RESULTS: HB-19 treatment of RET mice caused a significant delay in the onset of cutaneous tumors, several-months delay in the incidence of large tumors, a lower frequency of cutaneous nodules, and a reduction of visceral metastatic nodules while displaying no toxicity to normal tissue. Moreover, microvessel density was significantly reduced in tumors recovered from HB-19 treated mice compared to corresponding controls. Studies on the melanoma-derived tumor cells demonstrated that HB-19 treatment of TIII cells could restore contact inhibition, impair anchorage-independent growth, and reduce their tumorigenic potential in mice. Moreover, HB-19 treatment caused selective down regulation of transcripts coding matrix metalloproteinase 2 and 9, and tumor necrosis factor-α in the TIII cells and in melanoma tumors of RET mice. CONCLUSIONS: Although HB-19 treatment failed to prevent the development of spontaneous melanoma in the RET mice, it delayed for several months the onset and frequency of cutaneous tumors, and exerted a significant inhibitory effect on visceral metastasis. Consequently, HB-19 could provide a novel therapeutic agent by itself or as an adjuvant therapy in association with current therapeutic interventions on a virulent cancer like melanoma.